Optimization of cryopreserved single cell suspension of gastric epithelial cells for successful DotScanTM antibody microarray - Asif Sukri; Alfizah Hanafiah; Nik Ritza Kosai Nik Mahmood; Mustafa Mohamed Taher; Isa Mohamed Rose; Ramelah Mohamed (Penerbit Universiti Kebangsaan Malaysia, 2019)
Cell cryopreservation plays a pivotal role for successful immunological assays. DotScanTM antibody microarray employs live cells with satisfactory cell viability for detection of clusters of differentiation (CD) antigens in various diseases. Effective cryopreservation contributes to successful capture of cells on DotScanTM antibody microarray. The purpose of this study was to evaluate the effect of cells viability on cells binding to specific CD antigens. Cells with similar concentration but different percentage of cell viabilities were captured on DotScanTM slides. Cells stored for 5 days at -80ºC and added with freezing medium in stepwise manner had higher viabilities as compared to cells stored for 6 months at -80ºC and added with freezing medium in direct manner (p=0.012). Cells with 88% viability had higher binding to CD44/CD29 control antibodies as compared to cells with 33% viability. Short-term storage of cells and the technique for freezing medium addition to cells play a critical role for successful cryopreservation of single cell suspension.